Multi-camera networks : principles and applications - Aghajan, Hamid K.; Cavallaro, Andrea (Elsevier, AP, 2009)
This book is the definitive reference in multi-camera networks. It gives clear guidance on the conceptual and implementation issues involved in the design and operation of multi-camera networks, as well as presenting the state-of-the-art in hardware, algorithms and system development. The book is broad in scope, covering smart camera architectures, embedded processing, sensor fusion and middleware, calibration and topology, network-based detection and tracking, and applications in distributed and collaborative methods in camera networks. This book will be an ideal reference for university researchers, R & D engineers, computer engineers, and graduate students working in signal and video processing, computer vision, and sensor networks. . The first book, by the leading experts, on this rapidly developing field with applications to security, smart homes, multimedia, and environmental monitoring . Comprehensive coverage of: fundamentals, algorithms, design methodologies, system implementation issues, architectures, and applications . Presents in detail the latest developments in: multi-camera calibration, active and heterogeneous camera networks, multi-camera object and event detection, tracking, coding, smart camera architecture and middleware.